Going to the dentist - Civardi, Anne.; Bates, Michelle; Cartwright, Stephen, 1947- (London : Usborne, 2009)
Jake and Jessie Judd pay their first visit to the dentist where they both have check-ups and Jake gets a filling.
2.0
K-3
Keywords: Dental care -- Juvenile fiction; Dental care -- Fiction; Dental care -- Fiction; Picture books for children